Policies of Establishing Networks for Scientific and Technological Information Organization for Scientific Research and Innovation in Vietnam - Le, Tung Son (H. : ĐHQGHN, 2020)
In the context of the information society and knowledge economy, in order to meet the information access needs of organizations, individuals and businesses, it is essential to formulate policies for establishing scientific and technological information organization networks for scientific research and innovation in Vietnam. Based on the overview of experience in setting up scientific and technological information organization networks in some Asian countries, thereby the study has identified trends in setting up scientific and technological information organization networks and analyze the current situation of policies on establishing scientific and technological information organization networks in Vietnam. The study has identified the basic foundations in policies of setting up scientific and technological information organization networks, then making recommendations for completion the policies.